PROTOTIPE PEMILAH SAMPAH OTOMATIS BERBASIS ARDUINO UNO DENGAN NOTIFIKASI SMS GATEWAY DI SMP.S TERPADU SYEKH MUHAMMAD JA’FAR BANYORANG KABUPATEN BANTAENG - Hastuti; Andi Candra; Juniarti Iryani (CV. LAJAGOE PUSTAKA, 2023)
This study aims to: (1) This study aims to design an arduino uno-based automatic waste sorting prototype with SMS gateway notifications at Sheikh Muhammad Ja'far Integrated Middle School, (2)implement an arduino uno-based automatic waste sorting prototype (3)and find out the response of school principals, teachers, students to the waste sorting prototype. arduino uno based automation with SMS gateway notifications.The author makes observations at the research site to find problems that will be used as the basis for research and to get solutions that can overcome existing problems, then the author collects information by conducting direct interviews with the Principal about how waste management is at the school, then the author conducts a design waste temperature prototype product by combining all the components of the tool used to create an arduino uno-based automatic waste sorting prototype with an SMS gateway notification, then the authors validate the design of the tool that has been made. The author conducts validation tests on one lecturer who is an expert in this field, then the author tests the tools that have been made. Tool trials were carried out at the research site.The results of this study obtained an automatic waste sorting prototype with SMS Gateway notifications that can function properly by combining arduino uno, servo motors, inductive capacitive proximity sensors, ultrasonic sensors, and SIM modules. Implementing an arduino uno-based waste sorting prototype with SMS gateway notifications by bringing the device to school and storing it there. school principals, teachers and students give good responsibility to the existence of these tools. Because, provide benefits and will have an impact on the schoool environment.